P18 An audit on the delivery of Bristol Royal Children's Hospital paediatric orthopaedic services in response to BOAST COVID-19 guidance. (8th April 2021) - Benning, Matthew Singh; Berwin, James; Knapper, Thomas; Crosswell, Sebastien; Carpenter, Charlotte; Kenall, John; Monsell, Fergal; Thomas, Simon; Benning, Matthew Singh
Abstract: Introduction: The COVID-19 pandemic raised concerns regarding the spread of infection by asymptomatic children. Guidance from the British Orthopaedic Association Standards for Trauma (BOAST) for the 'management of patients with urgent orthopaedic conditions and trauma during the coronavirus pandemic', helped structure our service in response to the pandemic. We assessed our compliance with 'BOAST COVID-19 standards' pertaining to children to determine whether it is possible to run a safe and effective paediatric orthopaedic service. Methods: Between the 16th March and 30th April 2020, we performed a prospective audit of clinic and theatre data from the paediatric orthopaedic department at the Bristol Royal Children's Hospital against the 'BOAST COVID-19 standards'. We also performed a retrospective audit between 16th March and 30th April 2019 for comparison. Results: Patients booked into acute fracture clinic (AFC) and fracture clinic follow-up (FFO) reduced by 40% and 48% respectively from 2019 to 2020. A virtual fracture clinic (VFC) was implemented with increasing trend in VFC consultations. From 2019 to 2020, the number of patient initiated follow-up appointments increased in AFC and FFO from 16% to 75% and 12% to 35% respectively. Radiography was reduced; only 17% and 39% of AFC and FFO patients respectively required radiographs. On-call referrals and trauma cases reduced by almost 50% with a similar case mix year-on-year. All elective operating was cancelled in 2020. Conclusion: By reducing clinic admissions and theatre throughput, it was possible to run an effective paediatric orthopaedic service in a busy tertiary referral centre. Our aim now is to determine the long-term efficacy.